High resolution copy number analysis of IRF4 translocation‐positive diffuse large B‐cell and follicular lymphomas1. Issue 2 (17th October 2012) - Salaverria, Itziar; Martin‐Guerrero, Idoia; Burkhardt, Birgit; Kreuz, Markus; Zenz, Thorsten; Oschlies, Ilske; Arnold, Norbert; Baudis, Michael; Bens, Susanne; García‐Orad, Africa; Lisfeld, Jasmin; Schwaenen, Carsten; et al.
Abstract: Translocations affecting chromosome subband 6p25.3 containing the IRF4 gene have been recently described as characteristic alterations in a molecularly distinct subset of germinal center B‐cell‐derived lymphomas. Secondary changes have yet only been described in few of these lymphomas. Here, we performed array‐comparative genomic hybridization and molecular inversion probe microarray analyses on DNA from 12 formalin‐fixed paraffin‐embedded and two fresh‐frozen IRF4 translocation‐positive lymphomas, which together with the previously published data on nine cases allowed the extension of copy number analyses to a total of 23 of these lymphomas. All except one case carried chromosomal imbalances, most frequently gains in Xq28, 11q22.3‐qter, and 7q32.1‐qter and losses in 6q13‐16.1, 15q14‐22.31, and 17p. No recurrent copy‐neutral losses of heterozygosity were observed. TP53 point mutations were detected in three of six cases with loss of 17p. Overall this study unravels a recurrent pattern of secondary genetic alterations in IRF4 translocation‐positive lymphomas. © 2012 Wiley Periodicals, Inc.